Obesity prevalence and determinants among young adults, with special focus on normal-weight obesity; a cross-sectional study in Mumbai - Rujuta Sachin Hadaye; Rukman Mecca Manapurath; Barsha Pathak Gadapani (Wolters Kluwer Medknow Publications, 2020)
Background: India has >135 million obese individuals at present. Body mass index (BMI) has been used to assess obesity until recent times. Later, studies have shown that central body fat (BF) measurements as a reliable predictor of metabolic diseases. Hence, normal-weight obesity (NWO) is defined. Those with a normal range of BMI but increased fat percentage are found to be having metabolic syndromes at a very early life. The young adult group is specifically focused on the study with diet and physical activity as potential determinants; as an intervention at the right time can prevent the development of many noncommunicable diseases. Objectives: The aim of this study is to estimate the prevalence of obesity and its determinants with special reference to NWO. Materials and Methods: A cross-sectional study was conducted based on diet, physical activity, and other lifestyle factors on a sample of 269 young adults. Using Harpenden skinfold calipers, BF percentage was calculated based on Jackson and Pollock and Siri's equation. Binary logistic regression was also applied appropriately. Results: The proportion of obesity was 42.01%, and that of NWO was 16.1%. Sex, high protein diet, number of restaurant visits, less homemade tiffin intake, heavy physical activity, alcohol intake were found to be significantly associated with obesity. Intake of fish, physical activity, protein diet, day-time sleep were found to be significantly associated with NWO. Conclusion: The study emphasizes the need for including BF percentage in addition to BMI in regular clinical practice. It may help in preventive and promotive efforts.